(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: We aimed to investigate prospectively the prevalence of premenstrual symptoms (PSM), changes in blood pressure with menstrual cycles and to investigate the relative severity of each symptoms and to cluster these symptoms into factors, and the relative contributions of each factor in a sample of undergraduate students of Ahmadu Bello University, Zaria and Bingham University, Karu. A total of 370 female undergraduate students reported on the severity of 23 PMS in a full cycle. Their blood pressures (BP) were measured during follicular and luteal phases. Paired sample student t-test was used to investigate difference in mean of blood pressures based on menstrual phases. We fitted PCA to cluster the symptoms. Backache, wish to be alone, joint or muscle pain, fatigue, and pain in the thigh were the five most frequently reported symptoms. About 89% of the participants reported experiencing at least one symptom during each cycle. Mean arterial blood pressure, systolic, and diastolic blood pressures were significantly (P <0.001) higher at the luteal phase than at the follicular phase while, pulse rate was significantly higher (P <0.001) at the follicular phase than the luteal phase. The 23 symptoms were reduced into four clusters; affective, physical, somatic, and GIT/physical symptoms. In conclusion, our findings indicate a high prevalence of PMS with majority indicating that the symptoms as mild to severe. Blood pressure significantly increased at luteal phase than follicular phase. The 23 symptoms were reduced into four clusters.